Differentiating gastric schwannoma from gastric stromal tumor (≤5 cm) by histogram analysis based on iodine-based material decomposition images: a preliminary study - Wang, Gang; Liu, Xianwang; Zhou, Junlin (Frontiers in Oncology, 2023)
Abstract Objective: To investigate the value of histogram analysis based on iodine-based material decomposition (IMD) images obtained through dual-energy computed tomography (DECT) for differentiating gastric schwannoma (GS) from the gastric stromal tumor (GST) (≤5 cm), preoperatively. Methods: From January 2015 to January 2023, 15 patients with GS and 30 patients with GST (≤5 cm) who underwent biphasic contrast-enhanced scans using DECT were enrolled in this study. For each tumor, we reconstructed IMD images in the arterial phase (AP) and venous phase (VP). Nine histogram parameters were automatically extracted and selected using MaZda software based on IMD of AP and VP, respectively, including mean, 1st, 10th, 50th, 90th, and 99th percentile of iodine concentration value (Perc.01, Perc.10, Perc.50, Perc.90, Perc.99), variance, skewness, and kurtosis. The extracted IMD histogram parameters were compared by the Mann-Whitney U test. The optimal IMD histogram parameters were selected by receiver operating characteristic curves (ROC). Results: Among IMD histogram parameters of AP, the mean, Perc.50, Perc.90, Perc.99, variance, and skewness of the GS group were lower than that of the GST group (all P<0.05). Among the IMD histogram parameters of VP, Perc.90, Perc.99, and the variance of the GS group was lower than those of the GST group (all P<0.05). ROC analysis showed that Perc.99 (AP) generated the best diagnostic performance with the area under the curve, sensitivity, and specificity were 0.960, 86.67%, and 93.33%, respectively, when using 71.00 as the optimal threshold. Conclusion: Histogram analysis based on IMD images obtained through DECT holds promise as a valuable tool for the preoperative distinction between GS and GST (≤5 cm).